Anesthesiologists knowledge about anesthesiology care in patients with COVID-19 (Research, Society and Development, 2021)
COVID-19 is caused by SARS-CoV-2 betacoronavirus. The clinical manifestations consist of nonspecific signs and symptoms such as fever, dry cough, dyspnea, myalgia, fatigue, headache, anosmia and gastrointestinal symptoms. The recommendation for invasive airway management in patients with COVID-19 is using rapid sequence orotracheal intubation. This and other anesthetic procedures generates aerosols, so its essential to protect healthcare professionals with Personal Protective Equipment (PPE). Thus, this study sought to evaluate the use of PPE and also the knowledge of anesthesiologists in the management of patients with COVID-19. Of the 53 professionals interviewed, 13 (24,5%) reported that they did not had access to the PPE necessary for their safety in at least one procedure. This is a possibly factor related to the high prevalence of COVID-19 illness in the sample of professionals participating in the study (30,2%). In addition, 28,3% of the survey participants incorrectly calculated the tidal volume of a fictious patient. Thus, we concluded that procedures performed by these professionals are partially adequate for COVID-19 patients in perioperative management according to the literature consulted. Therefore, continued education measures are essential to increase doctor’s assertiveness in the conducts. Furthermore, health institutions must provide necessary PPE to healthcare professionals to reduce the chance of infection of these workers.